Determination of IC50 Root Extracts of Bajakah Tampala (Spatholobus littoralis Hassk) and Kalalawit (Uncaria gambir Roxb) Using DPPH Method - Melsya Merdita; Rizki Febriyanti; Wilda Amananti (Jurnal Ilmiah Teknik Kimia, 2023)
Indonesia is one of the countries whose people use traditional medicine as an alternative medicine to treat various types of diseases, one of which is by using bajakah root. The purpose of this study was to determine the value of IC50 and compare the antioxidant activity of the steel root extract of tampala and kalalawit types. Research methods using experimental methods. The population used is the root of bajakah type tampala and kalalawite. Samples were obtained from an online shop with a simple random sampling technique.  Extracted using the reflux method. Determination of IC50 using the DPPH method (1,1- diphenyl-2- picrilhydrazyl). The results of the research on the IC50 value obtained from the roots of bajakah tampala are 46.7304 ppm, which is classified as having anti-ochistic activity and is very strong because it <50 ppm and kalalawit bajakah root of 53.1006  ppm is classified as having strong antioxidant activity because it >50-100 ppm. However, when compared to the vitamin C comparison solution which has a  lower value of IC50,  which is  14.6217 ppm, it has very strong antioxidant activity. The efficacy of this study value of IC50 in the roots of the tampala type of steel is lower, indicating a stronger antioxidant activity than the roots of the kalalawit type bajakah.